PENERAPAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAM ACHIEVMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS MATERI KEANEKARAGAMAN SUKU BANGSA PADA SISWA KELAS VI SD NEGERI 3 LUENG PUTU - Siti Rosnidah (Universitas Jabal Ghafur, 2020)
The purpose of this study was to describe the quality of social studies learning through the type of STADm in class VI students of SD Negeri 3 Lueng Putu. This classroom action research was carried out in two cycles. Each cycle consists of planning, implementation, observation, reflection. The research subjects were teachers, class VI students at SD Negeri 3 Lueng Putu. The technique of collecting data uses tests and non-tests. Data analysis used quantitative and qualitative descriptive analysis. The results of the study showed: (1) The skill of the first cycle teacher got a score of 19 good categories, and the second cycle of the score 30 was very good. (2) Activity of the first cycle students get a score of 17.14 enough categories, and the second cycle scores 25.32 in the good category. (3) The percentage of classical completeness in student learning outcomes in cycle 1 is 55%, and increases in cycle 2 to 91%. The conclusion of the study through the type of STAD can improve the quality of social studies learning including teacher skills, student activities, learning outcomes of SD Negeri 3 Lueng Putu. It is recommended that teachers apply STAD type cooperative learning so students can learn actively and independently Keywords: Cooperative Learning Student Team Achievement Division (Stad) Type, Learning Outcomes.